Group portrait of the attendees of the first P.T.A. Convention - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the first P.T.A. (Parent Teacher Association) Convention, held 1936 in San Jose, California. Photo was taken in front of the San Jose Civic Auditorium.